2015
DOI: 10.1155/2015/602425
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Chemical Compounds Isolated from the Rhizome ofSmilax glabraon Nitric Oxide and Tumor Necrosis Factor-αProduction in Lipopolysaccharide-Induced RAW264.7 Cell

Abstract: The rhizome of Smilax glabra has been used for a long time as both food and folk medicine in many countries. The present study focused on the active constituents from the rhizome of S. glabra, which possess potential anti-inflammatory activities. As a result, nine known compounds were isolated from the rhizome of S. glabra with the bioassay-guiding, and were identified as syringaresinol (1), lasiodiplodin (2), de-O-methyllasiodiplodin (3), syringic acid (4), 1,4-bis(4-hydroxy-3,5-dimethoxyphenyl)-2,3-bis(hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
(41 reference statements)
1
10
0
1
Order By: Relevance
“…Evidence is accumulating that A. galanga , which contains terpenes and flavonoids, has strong antioxidant activity and significantly reduces the expression of the NF- κ B signaling biomarker [ 10 ] leading to a decrease of cytokine production by T-cells [ 27 ]. Astilbin, which is isolated from S. glabra , has significantly inhibitory effects on nitric oxide, TNF- α , and IL-6 production [ 28 ] through p65, ERK1/2, and JNK pathways [ 29 ]. In addition, anti-inflammatory, antiproliferative, and antioxidant activities have been well documented for S. corbularia [ 30 ], R. nasutus [ 31 , 32 ], A. ebracteatus [ 33 ], S. involute , S. collinsae [ 34 ], and Smilax sp.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is accumulating that A. galanga , which contains terpenes and flavonoids, has strong antioxidant activity and significantly reduces the expression of the NF- κ B signaling biomarker [ 10 ] leading to a decrease of cytokine production by T-cells [ 27 ]. Astilbin, which is isolated from S. glabra , has significantly inhibitory effects on nitric oxide, TNF- α , and IL-6 production [ 28 ] through p65, ERK1/2, and JNK pathways [ 29 ]. In addition, anti-inflammatory, antiproliferative, and antioxidant activities have been well documented for S. corbularia [ 30 ], R. nasutus [ 31 , 32 ], A. ebracteatus [ 33 ], S. involute , S. collinsae [ 34 ], and Smilax sp.…”
Section: Discussionmentioning
confidence: 99%
“…A. galanga can also reduce the expression of NF- κ B signaling biomarkers via an increased expression of a molecule inhibiting NF- κ B (TNFAIP3) [ 10 ], leading to a decrease in cytokine production by T cells [ 31 ]. Other studies reported that the flavonoid astilbin isolated from the rhizome of S. glabra , another major active component of WCR, has an inhibitory effect on Jak/Stat3 signaling in Th17 cells [ 32 ] and inhibits production of nitric oxide, TNF- α , and IL-6 production [ 33 ] through p65, ERK1/2, and JNK pathways [ 34 ]. Astilbin also downregulates T cell function by suppressing activated T cell migration and adhesion and stimulating negative regulatory interleukin 10 (IL-10) production [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…So, the structure of 7 was attested as syringaresinol. [10] 4. CONCLUSION Five triterpenoids, 24-methylenecycloartanol (1), (23Z)-cycloart-23-en-3,25-diol (2), mollic acid (3), ursolic acid (4), 3-hydroxyurs-11-en-28,13-olide (5), two other compounds, one C11-norisoprenoid, loliolide (6), and one lignan, syringaresinol (7) were recognized by extensive analysis of HR-ESI-MS, and NMR data.…”
Section: C30h48o3 By Hr-esi-ms Data ([M-h] -mentioning
confidence: 99%